Making sense of HIV/AIDS gender issues in Butterworth (Eastern Cape Province), South Africa - Nyhiba, Tandisile (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2011.